2017
DOI: 10.1080/09168451.2017.1282808
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of soy lipophilic proteins: comparison with other soy protein fractions

Abstract: Solubility of soy lipophilic proteins (LP) was studied as compared with that of other soy protein fractions. LP, β-conglycinin, glycinin, and soy protein isolate (N-SPI) were prepared under the condition to avoid heat denaturation. Solubility of LP was lower than that of other soy protein fractions under all the tested conditions varying in pH values and ionic strength. The solubility of LP was increased constantly by elevating temperature until 90 °C, whereas that of β-conglycinin and glycinin dropped at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…SPI mainly consists of two globulin proteins: 7S (β-conglycinin) and 11S (glycinin) . Since the solubility of these globulin proteins is reported to be very good at neutral pH and temperature range of 50–80 °C, it is therefore envisaged that SPI can show good solubility under the experimental conditions (pH > 7 at 60 °C) considered in this work. SPI has been reported to show high solubility at pH ≤3 and pH ≥6 and the least solubility at pH 4.5 =pI (isoelectric point). , Possibly, during blending of PVA and SPI in distilled water at pH ∼7.8, protons get extracted from the carboxylic acid of SPI to form carboxylate ions.…”
Section: Discussionmentioning
confidence: 98%
“…SPI mainly consists of two globulin proteins: 7S (β-conglycinin) and 11S (glycinin) . Since the solubility of these globulin proteins is reported to be very good at neutral pH and temperature range of 50–80 °C, it is therefore envisaged that SPI can show good solubility under the experimental conditions (pH > 7 at 60 °C) considered in this work. SPI has been reported to show high solubility at pH ≤3 and pH ≥6 and the least solubility at pH 4.5 =pI (isoelectric point). , Possibly, during blending of PVA and SPI in distilled water at pH ∼7.8, protons get extracted from the carboxylic acid of SPI to form carboxylate ions.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the solubility of SPI is low, [52] leading to high surface hydrophobicity [61]. The reason has been attributed to the denaturation induced by heating, drying, and storage conditions [62,63]. A recent study showed that β-carotene bioaccessibility was highly related to the type of proteins used to stabilize the emulsions [64].…”
Section: Discussionmentioning
confidence: 99%
“…On addition, the changes in conformation of structure also can explain the reason for increasing in solubility. Solubility of proteins is influenced by pH, ionic strength, type of salts, and protein conformation (Sirison et al, 2017). According to the results of conformation analysis ( Figure 2B) the unfolding of the glycosylated hydrolysate chains and loosening tertiary conformation might promote intramolecular hydration of proteins.…”
Section: Discussionmentioning
confidence: 99%